2016
DOI: 10.1039/c5ra19511j
|View full text |Cite
|
Sign up to set email alerts
|

Acetone as a polar cosolvent for pyridinium-based ionic liquids

Abstract: The work reports transport and structure properties of the three pyridinium-based ionic liquids (RTILs) -N-butylpyridinium hexafluorophosphate [BPY][PF 6 ], N-butylpyridinium trifluorosulfonate [BPY][TF] and N-butylpyridinium bis(trifluoromethanesulfonyl)imide [BPY][TFSI] -in their mixtures with acetone (ACET). The ionic conductivity maximum occurs at 10 mol% RTIL, irrespective of the anion. The absolute ionic conductivity value of [BPY][TF] is higher than those of other RTILs. This is explained by a weaker ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…Ionic liquids (ILs) are formed by ions with molecular characteristics such as bulky and asymmetric structures, delocalized charge, low charge density, presence of nonpolar alkylic chains and a proposed dual ionic and organic nature, which are the reason of their low melting temperature due to their effect on microscopic level features and intermolecular interactions [1][2][3]. These characteristics determine the properties and structure of pure ILs but also have a large effect when mixing with molecular solvents (MSs) [4][5][6][7]. Intermolecular forces between ILs and MSs are largely complex [810], even with the appearance of competition effects between the involved ions and molecules [11], because of their dependence on the protic or aprotic, polar or apolar, or hydrogen bonding ability of the MSs, and show remarkable changes with mixture composition, pressure and temperature [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Ionic liquids (ILs) are formed by ions with molecular characteristics such as bulky and asymmetric structures, delocalized charge, low charge density, presence of nonpolar alkylic chains and a proposed dual ionic and organic nature, which are the reason of their low melting temperature due to their effect on microscopic level features and intermolecular interactions [1][2][3]. These characteristics determine the properties and structure of pure ILs but also have a large effect when mixing with molecular solvents (MSs) [4][5][6][7]. Intermolecular forces between ILs and MSs are largely complex [810], even with the appearance of competition effects between the involved ions and molecules [11], because of their dependence on the protic or aprotic, polar or apolar, or hydrogen bonding ability of the MSs, and show remarkable changes with mixture composition, pressure and temperature [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…TSILs suffer from a huge increase in viscosity when loaded with CO 2 due to the hydrogen bonding (H-bonding) network between the carbamate and ammonium counterparts. This could be overcome by following different strategies such as incorporating an aprotic heterocyclic anion 36 or mixing TSILs with low-viscosity solvents 37 (more reviews regarding using TSILs for capturing CO 2 can be found elsewhere 33 , 38 ).…”
Section: Introductionmentioning
confidence: 99%
“…N-Butylpyridinium tetrafluoroborate, [BPY][BF 4 ], was used as a solvent due to a fundamental interest in the pyridiniumbased ILs. [30][31][32][33][34][35][36][37] Furthermore, imidazolium-based tetrafluoroborates are widely investigated in various contexts, whereas information on the pyridinium-based tetrafluoroborates is scarce yet. A few concentrations of nanodiamonds (NDs, 42 atoms) and singlewalled (5,5) CNTs (120 atoms) in [BPY][BF 4 ] were explored.…”
Section: Introductionmentioning
confidence: 99%